Adsorption filter and filter unit

The laminated adsorption filter with a specific range of activated carbon particle sizes and a structured substrate configuration addresses the issues of filter collapse and performance variability, achieving efficient VOC removal with low pressure loss.

JP2025049864APending Publication Date: 2025-04-04TOYOBO MC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023158333
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing adsorption filters face issues with collapse due to external forces, leading to increased pressure loss and irregular performance variations, especially when the aggregates are irregularly structured.

Method used

A laminated adsorption filter structure comprising at least a substrate A, an adsorption layer with activated carbon of average particle diameter 300 μm to 700 μm, and a substrate B, where the quality factor value is 0.8 or more, and the substrates are preferably thermal bonded nonwoven fabrics or spunbonded nonwoven fabrics.

Benefits of technology

The proposed adsorption filter achieves efficient adsorption of volatile organic compounds with low pressure loss, ensuring consistent performance and improved processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025049864000001
    Figure 2025049864000001
Patent Text Reader

Abstract

To provide an adsorption filter having high adsorption performance and low pressure loss.SOLUTION: An adsorption filter according to the present invention comprises at least a substrate A, an adsorption layer, and a substrate B, laminated in the stated order. The adsorption layer contains activated carbon, and the activated carbon has an average particle diameter of 300 to 700 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adsorption filter and a filter unit. [Background technology]

[0002] In recent environmental society, interest in odor pollution countermeasures has been growing. For example, odor pollution is pollution caused by exhaust gas. Among exhaust gases, volatile organic compounds such as toluene and acetaldehyde are considered to be causative substances of sick house syndrome, and the removal and deodorization of these odorous substances is a major issue. It is known that these exhaust gases can be adsorbed and removed by filters attached to air purification devices such as air purifiers and air conditioners. It is preferable that this filter has low pressure loss, i.e., high breathability.

[0003] In order to remove pollutants with high efficiency, there is a high demand for filters with high adsorption performance and low pressure loss. In response to this demand, for example, Patent Document 1 discloses that activated carbon particles of the same particle diameter are bonded and aggregated with a thermoplastic resin to form irregular aggregates, thereby forming voids between the aggregates, thereby realizing low pressure loss. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 3612329 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the filter of Patent Document 1 has problems such as the aggregates breaking down due to external forces applied during sheet formation, filling voids and increasing pressure loss, and the molded aggregates having an irregular structure, resulting in large variations in performance.

[0006] Therefore, the present invention has been made in consideration of the problems inherent in the above-mentioned techniques, and an object of the present invention is to provide a high-performance adsorption filter with low pressure loss. [Means for solving the problem]

[0007] The present inventors have conducted intensive research to solve the above problems and have finally completed the present invention.

[0008] 1. An adsorption filter in which at least a substrate A, an adsorption layer, and a substrate B are laminated in the stated order, the adsorption layer contains activated carbon, and the average particle length of the activated carbon is 300 μm to 700 μm. 2. The adsorption filter according to claim 1, characterized in that the quality factor value represented by the following formula is 0.8 or more. Quality factor value = -Ln{(100 - toluene deodorization efficiency [%]) / 100} / pressure loss in adsorption layer [mmAq] 3. The adsorption filter according to claim 1 or 2, characterized in that the substrate A is a thermally bonded nonwoven fabric or a spunbonded nonwoven fabric. 4. The adsorption filter according to claim 1 or 2, characterized in that the substrate B is a needle-punched nonwoven fabric, a thermally bonded nonwoven fabric, a melt-blown nonwoven fabric, or a spun-bonded nonwoven fabric. 5. A filter unit using the adsorption filter according to claim 1 or 2. Effect of the Invention

[0009] According to the present invention, it is possible to provide an adsorption filter capable of efficiently adsorbing removed substances with low pressure loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Although an embodiment of the present invention will be described below, the present invention is not limited to the following, and an optimum configuration can be selected for each application in accordance with the spirit of the present invention.

[0011] The adsorption filter of the present invention is composed of at least a substrate A, an adsorption layer, and a substrate B laminated in the order described above, and the adsorption layer contains activated carbon.

[0012] The average particle length of the activated carbon contained in the adsorption layer of the present invention is preferably 300 to 700 μm, more preferably 350 to 650 μm. Within the above range, even if the activated carbon basis weight is increased to obtain a certain adsorption performance, the voids are maintained between the activated carbon particles, and low pressure loss can be obtained. When the average particle length is less than 300 μm, increasing the amount of activated carbon to obtain adsorption performance reduces the voids and increases the pressure loss. When the average particle length is greater than 700 μm, the particles are more likely to fall out from between the substrates, and the processability during folding and corrugation when the air purification filter unit is made into a pleated or wavy shape is poor.

[0013] The average particle major axis can be, for example, the average of the 100 measurements obtained by observing 100 pieces of activated carbon with an SEM, measuring the length of the longest line segment among the lines connecting the outer edges of one particle. In the micrograph, if the shape of the particle is circular, the length of the line segment is the diameter of the circle, if the shape of the particle is elliptical, the length of the line segment is the major axis of the ellipse, and if the shape of the particle is rectangular, the length of the line segment is the length of the long side of the rectangle, but the shape of the particle is not limited to the above shapes. Whatever the shape of the particle, the major axis can be uniquely determined by the above definition.

[0014] The particle size range of the activated carbon contained in the adsorption layer of the present invention is not particularly limited, but taking into consideration the breathability, the fall-off of the activated carbon, and the sheet processability, for example, the value according to the ASTM standard sieve (ASTM E11) is preferably 150 to 1000 μm, more preferably 180 to 850 μm. If the particle size range is less than 100 μm, increasing the weight of the activated carbon to obtain a certain level of adsorption performance reduces the voids and increases the pressure loss. If the particle size range is more than 1000 μm, the activated carbon may fall off from the adsorption filter, or the processability may be poor in pleating or wavy processing when forming an air purification filter unit having a pleated or wavy shape.

[0015] The activated carbon is not particularly limited, but it is preferable to use common activated carbon such as coconut shell activated carbon, coal-based activated carbon, wood-based activated carbon, and synthetic resin-based activated carbon in terms of performance and availability.

[0016] The BET specific surface area of ​​the activated carbon is not particularly limited, but is preferably 800 to 1500 m 2 / g is preferable, and 850 to 1300m 2 / g is more preferable in terms of performance. 2 If the specific surface area is less than 1500 m / g, it is difficult to obtain the desired performance. 2 If the amount exceeds 1 / g, it is likely to be desorbed from the adsorption filter.

[0017] The pore volume of the activated carbon is not particularly limited, but is preferably 0.30 to 0.70 cm 3 / g is preferable, and 0.40 to 0.55 cm 3 / g is more preferable. 3 When the pore volume is less than 0.70 cm3 / g, it is difficult to obtain sufficient adsorption performance. 3 If the amount exceeds 1 / g, it is likely to be desorbed from the adsorption filter.

[0018] The average pore size of the activated carbon can be adjusted appropriately depending on the object to be adsorbed. For example, when the object to be adsorbed is toluene, the average pore size is preferably 15 Å to 19 Å, and more preferably 16 Å to 18 Å. However, there is no particular limitation.

[0019] The weight of the activated carbon in the adsorption filter of the present invention is 50 to 700 g / m 2 is preferable, and 100 to 600 g / m 2 Within this range, a significant increase in pressure loss can be suppressed and sufficient deodorizing performance can be obtained. 2 If the weight of the activated carbon is less than 700g / m, it will not exhibit sufficient adsorption performance. 2If the particle size is larger than this, the particles may fall off from the adsorption filter, or the processability of pleating or corrugating may be deteriorated when the particles are made into an air purification filter unit having a pleated or corrugated shape.

[0020] The adsorption layer can efficiently adsorb and remove volatile organic compounds. The activated carbon may be treated with chemicals to improve the adsorption performance of polar substances and aldehydes. Chemicals used in gas chemical treatment include, for example, amine-based agents such as ethanolamine, polyethyleneimine, aniline, p-anisidine, and sulfanilic acid for aldehyde gases, nitrogen compounds such as NOx, sulfur compounds such as SOx, and acidic polar substances such as acetic acid; sodium hydroxide, potassium hydroxide, guanidine carbonate, guanidine phosphate, aminoguanidine sulfate, 5,5-dimethylhydantoin, benzoguanamine, 2,2-iminodiethanol, 2,2,2-nitrotriethanol, ethanolamine, and the like. Suitable chemicals include amine hydrochloride, 2-aminoethanol, 2,2-iminodiethanol hydrochloride, p-aminobenzoic acid, sodium sulfanilate, L-arginine, methylamine hydrochloride, semicarbazide hydrochloride, hydrazine, hydroquinone, hydroxylamine sulfate, permanganate, potassium carbonate, and potassium hydrogen carbonate. For basic polar substances such as ammonia, methylamine, trimethylamine, and pyridine, suitable chemicals include phosphoric acid, citric acid, malic acid, ascorbic acid, and tartaric acid. The chemical treatment is carried out, for example, by supporting or impregnating the activated carbon with the chemical. In addition to treating the activated carbon directly with the chemical, it is also possible to impregnate the activated carbon near the surface of the adsorption filter by a normal coating method or to impregnate the entire adsorption filter. In this case, it is also possible to prepare a chemical aqueous solution containing a thickener such as sodium alginate or polyethylene oxide, and then support or impregnate the activated carbon. This method is effective in supporting and impregnating chemicals that have low solubility in water, and also in preventing the chemicals from falling off.

[0021] The adsorption layer may further contain an adhesive. Examples of the adhesive include thermoplastic powder resins and hot melt sheets (e.g., spider web hot melt sheets), among which thermoplastic powder resins are preferred. Powder resins can be uniformly dispersed in the activated carbon. Types of thermoplastic powder resins include polyolefin resins, polyamide resins, polyester resins, and ethylene-acrylic copolymer resins.

[0022] When a thermoplastic powder resin is used as the adhesive, the size of the resin is preferably 10 to 500 μm, more preferably 5 to 30 μm, in terms of average particle diameter. It is also desirable that 95% by weight or more of the resin is contained in the range of 1 to 40 μm in average particle diameter. If the average particle diameter is within this range, the thermoplastic resin can be prevented from blocking the surface pores of the activated carbon, while pre-adhesion to the activated carbon by van der Waals forces or electrostatic forces during mixing with the activated carbon can be effectively achieved, allowing the resin to be uniformly dispersed, and it is possible to effectively prevent partial peeling between the adsorption layer and the substrate.

[0023] The shape of the thermoplastic powder resin used in the adhesive is not particularly specified, but examples include spherical and crushed shapes. Of course, two or more types of thermoplastic powder resins can be used in combination. Furthermore, even if a chemically supported activated carbon or a chemically supported substrate is used, with this formulation, the thermoplastic powder resin is temporarily bonded to the surface of the activated carbon from the time of mixing in a dry state, so that even if the chemicals have different properties, they can be prevented from interfering with each other in the subsequent sheeting process, and sufficient effects can be achieved.

[0024] The thermoplastic resin powder is preferably used in an amount of 1 to 40% by weight, more preferably 3 to 30% by weight, relative to the activated carbon. Within this range, an adsorption filter excellent in adhesion to the substrate A and the substrate B, pressure loss, and deodorizing performance can be obtained.

[0025] The quality factor value of the adsorption filter of the present invention, as shown in the following formula, is preferably 0.8 or more, and more preferably 1.0 or more. The higher the quality factor value, the better the adsorption performance and the lower the pressure loss. If the quality factor value is less than 0.8, there are problems such as low volatile organic compound removal performance, high pressure loss, or both. Quality factor value = -Ln{(100 - toluene deodorization efficiency [%]) / 100} / pressure loss in adsorption layer [mmAq]

[0026] Various sheet-like substrates can be used for the substrate A and substrate B. As such a sheet-like substrate, a woven or nonwoven fabric having air permeability is preferable, and a nonwoven fabric is particularly preferable because the fibers are densely packed. As the nonwoven fabric, a dry nonwoven fabric such as a thermal bond nonwoven fabric, a needle punch nonwoven fabric, or a spunlace nonwoven fabric, a spunbond nonwoven fabric, a melt blown nonwoven fabric, or a wet nonwoven fabric is preferably used as appropriate depending on the application. The sheet-like substrate may be resin-processed. The sheet-like substrate may also be electret-processed.

[0027] The substrate A and the substrate B may be the same type of substrate or different types of substrates. Various combinations can be used as necessary.

[0028] The adsorption filter of the present invention may further contain components having additional functions such as antibacterial agents, antifungal agents, antiviral agents, and flame retardants. These components may be kneaded into the substrate A and / or substrate B, or may be attached and supported in post-processing. For example, by including a flame retardant, it is possible to manufacture an adsorption filter that meets the flame retardant standard specified in FMVSS.302 and the UL flame retardant standard. In addition, components having additional functions may be added to the adsorption layer.

[0029] Next, the method for producing the adsorption filter of the present invention will be described in detail. First, the activated carbon and adhesive are weighed out to a predetermined weight, placed in a stirrer, and stirred at a rotation speed of 30 rpm for about 10 minutes. Next, this mixed powder is scattered on the adhesive layer side of the substrate, and the substrate is further placed on top of it and subjected to a heat press treatment. The surface temperature during the heat press is preferably 3 to 30°C higher than the melting point of the thermoplastic resin, preferably 5 to 20°C higher.

[0030] The thickness of the adsorption filter is preferably 0.1 to 3.0 mm, more preferably 0.5 to 2.0 mm. If the thickness is less than 0.1 mm, the dust collection space is small, so that the pressure loss increases quickly when the dust load is applied, and clogging occurs. If the thickness exceeds 3.0 mm, the thickness is too thick, and when it is made into a pleated unit, the structural resistance increases, resulting in a practical problem of high pressure loss in the entire unit.

[0031] Examples of the method for finally heat-pressing the adsorption filter into a sheet include the roll-to-roll heat-press method commonly used in the field, and the flat-bed lamination method in which the filter is sandwiched between two flat heated belt conveyers on both sides. The flat-bed lamination method is more preferred because it produces a more uniform thickness and adhesive state.

[0032] When pleating the adsorption filter, a general pleating machine such as a reciprocating or rotary type can be used. In addition, a heat setting step may be performed to fix the height and pitch of the pleats to make it easier to attach the frame material and to stabilize the shape of the adsorption filter during use. The heat treatment temperature during heat setting is preferably equal to or higher than the melting start temperature (melting point -10 to 20°C) of the thermal adhesive fiber contained in the adhesive layer and equal to or higher than the melting start temperature of the thermal adhesive fiber contained in the adhesive layer. If the temperature is set to be equal to or lower than the melting point of +30°C, the pleats can be maintained without being adhered to each other, and the performance of the adsorption filter itself can be maintained.

[0033] After being processed and cut to the required dimensions, the adsorption filter can be used as a filter unit, either alone or in combination with a frame or the like. Thus, the filter unit is also included in the scope of the present invention. EXAMPLES

[0034] The effects of the present invention will be specifically shown below by way of examples. The following examples are not intended to limit the present invention, and any design modifications made in accordance with the spirit described above and below are within the technical scope of the present invention.

[0035] (Quality factor value evaluation) The quality factor value was calculated from the following formula using the evaluation of toluene removal performance and the evaluation of pressure drop in the adsorption layer, which will be described later. Quality factor value = -Ln{(100 - toluene deodorization efficiency [%]) / 100} / pressure loss in adsorption layer [mmAq]

[0036] (Evaluation of toluene removal performance) Area 36cm 2 An adsorption filter is sandwiched between and placed in the column. Air with a toluene vapor concentration of 80 ppm is supplied to the column under conditions of a surface velocity of 20 cm / s, a temperature of 25°C, and a humidity of 50% RH. The toluene concentration at the column outlet is measured after 1 minute, and the removal rate (η) is calculated by inputting the toluene inlet concentration (Ci [ppm]) and toluene outlet concentration (Co [ppm]) into the following formula. The toluene concentration is measured using a hydrocarbon meter. Removal rate η(%)=[1-(Co / Ci)]×100

[0037] (Evaluation of pressure drop in adsorption layer) The pressure drop (mmAq) of the adsorption layer is evaluated using the following procedure. (1) The adsorption filter is installed in a duct, the linear speed at which the sheet passes is controlled to 10.4 cm / sec, and the static pressure difference between the upstream and downstream of the sheet is read with a pressure gauge. (2) The adsorption layer is peeled off from the adsorption filter, and substrate A and substrate B are stacked without the adsorption layer, and the static pressure difference between the upstream and downstream is read with a pressure gauge using the above process. (3) The results of (1) and (2) are entered into the following formula to calculate the pressure drop of the adsorption layer. Pressure loss in adsorption layer [mmAp] = Pressure loss in adsorption filter [mmAp] - Pressure loss in substrate A and substrate B [mmAp]

[0038] Example 1 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1, and the mixture was applied to a sheet with a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0039] Example 2 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0040] Example 3 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0041] Example 4 Electrostatically treated needle punched nonwoven fabric (40g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0042] Example 5 Electrostatically treated needle punched nonwoven fabric (40g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0043] Example 6 Electrostatically treated needle punched nonwoven fabric (40g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0044] Example 7 Electrostatically treated needle punched nonwoven fabric (50g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0045] Example 8 Electrostatically treated needle punched nonwoven fabric (50g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0046] Example 9 Electrostatically treated needle punched nonwoven fabric (50g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0047] Example 10 Electrostatically treated needle punched nonwoven fabric (95g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0048] Example 11 Electrostatically treated needle punched nonwoven fabric (95g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0049] Example 12 Electrostatically treated needle punched nonwoven fabric (95g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0050] Example 13 Thermal bond nonwoven fabric (27g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0051] Example 14 Thermal bond nonwoven fabric (27g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0052] Example 15 Thermal bond nonwoven fabric (27g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0053] Example 16 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 400 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0054] Example 17 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle size Long axis: 400μm, specific surface area: 1000m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0055] Example 18 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 400 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0056] Example 19 A PET thermal bonded nonwoven fabric (first layer basis weight 30 g / m) having a first layer composed of a thermal bonded nonwoven fabric containing thermal adhesive staple fibers and a second layer composed of a nonwoven fabric containing high melting point fibers with a melting point 30°C higher than that of the thermal adhesive staple fibers with the lowest melting point in the first layer. 2 , second layer weight 40g / m 2 , total weight 70g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, an electrostatically treated meltblown nonwoven fabric (basis weight 26 g / m 2 The adsorption filter was obtained by laminating two pieces of the adsorption filter (tensile strength of 3N when the displacement is 3 mm) and integrating them by heat and pressure bonding. The physical properties of the adsorption filter were evaluated by the above-mentioned method.

[0057] Example 20 A PET thermal bonded nonwoven fabric (first layer basis weight 30 g / m) having a first layer composed of a thermal bonded nonwoven fabric containing thermal adhesive staple fibers and a second layer composed of a nonwoven fabric containing high melting point fibers with a melting point 30°C higher than that of the thermal adhesive staple fibers with the lowest melting point in the first layer. 2 , second layer weight 40g / m 2 , total weight 70g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, an electrostatically treated meltblown nonwoven fabric (basis weight 26 g / m 2 The adsorption filter was obtained by laminating two pieces of the adsorption filter (tensile strength of 3N when the displacement is 3 mm) and integrating them by heat and pressure bonding. The physical properties of the adsorption filter were evaluated by the above-mentioned method.

[0058] Example 21 A PET thermal bonded nonwoven fabric (first layer basis weight 30 g / m) having a first layer composed of a thermal bonded nonwoven fabric containing thermal adhesive staple fibers and a second layer composed of a nonwoven fabric containing high melting point fibers with a melting point 30°C higher than that of the thermal adhesive staple fibers with the lowest melting point in the first layer. 2 , second layer weight 40g / m 2 , total weight 70g / m 2 ), granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, an electrostatically treated meltblown nonwoven fabric (basis weight 26 g / m 2 The adsorption filter was obtained by laminating two pieces of the adsorption filter (tensile strength of 3N when the displacement is 3 mm) and integrating them by heat and pressure bonding. The physical properties of the adsorption filter were evaluated by the above-mentioned method.

[0059] Comparative Example 1 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 250 μm, specific surface area 1000 m2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the resulting mixture had a basis weight of 300 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 ) are laminated and integrated by heat and pressure bonding to form an adsorption filter. The physical properties of this adsorption filter were evaluated by the above-mentioned methods.

[0060] Comparative Example 2 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 250 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​400 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0061] Comparative Example 3 Electrostatically treated needle punched nonwoven fabric (weight 30g / m 2 ), granular activated carbon (average particle diameter 250 μm, specific surface area 1000 m 2 / g) and thermoplastic powder resin were mixed in a weight ratio of 20:1 and the mixture was applied to a surface area of ​​500 g / m 2 On top of this, a thermal bond nonwoven fabric (65 g / m 2 The adsorption filter was evaluated for its physical properties by the above-mentioned methods.

[0062] [Table 1]

[0063] It can be seen from Table 1 that when the average particle length of activated carbon is 300 μm to 700 μm, the quality factor value is high and the pressure loss is low. [Industrial Applicability]

[0064] The adsorption filter of the present invention makes it possible to efficiently remove volatile organic compounds such as toluene and aldehydes with low pressure loss, and is therefore expected to make a great contribution to the industrial sector.

Claims

1. In an adsorption filter in which at least a substrate A, an adsorption layer, and a substrate B are laminated in the order described, The adsorption layer includes activated carbon, An adsorption filter, characterized in that the average particle length of the activated carbon is 300 μm to 700 μm.

2. The adsorption filter according to claim 1, characterized in that the quality factor value represented by the following formula is 0.8 or more. Quality factor value=−Ln{(100−toluene deodorization efficiency [%]) / 100} / pressure loss of adsorption layer [mmAq]

3. 3. The adsorption filter according to claim 1, wherein the substrate A is a thermal bonded nonwoven fabric or a spun bonded nonwoven fabric.

4. 3. The adsorption filter according to claim 1, wherein the substrate B is a needle-punched nonwoven fabric, a thermal-bonded nonwoven fabric, a melt-blown nonwoven fabric, or a spun-bonded nonwoven fabric.

5. A filter unit using the adsorption filter according to claim 1 or 2.

Citation Information

Patent Citations

  • Cohesive activated carbon air filter

    JP3612329B2